Investigation into crack healing of asphalt mixtures using healing agents. (10th February 2018) - Riara, Martin; Tang, Ping; Mo, Liantong; Javilla, Barugahare; Wu, Shaopeng
Highlights: Cracks in asphalt pavements can be healed effectively using healing agents. Crack healing depends on agent type, healing time and aging of mixture. Initial healing had the highest contribution to the ultimate healing. Multiple fracture-rehealing performance is useful in selection of healing agents. Re-healing performance is sensitive to the drying rate of healing agents. Abstract: This study investigated the crack healing ability of aged and unaged AC-13 basalt asphalt mixtures using five healing agents. Notched semicircular asphalt mixtures were cracked and healed using the healing agents and the recovered critical load at fracture was adopted as a healing indicator. Crack healing was found to be dependent on the type of healing agent, healing time and aging of mixture. A maximum healing up to 73% was obtained after 8 days of uninterrupted healing. Multiple fracturing-rehealing of the healed mixture didn't significantly affect the healing index (HI) of the successive cycles. The re-healing performance was sensitive to the drying rate of healing agents, and a high drying rate reduced the re-healing performance. The first day of healing had the highest contribution to the ultimate healing potential, and further increase in the healing duration resulted in a steady increase in healing index. The high healing performance indicated that carefully selected healing agents have the potential to heal cracks in asphalt pavements.